Procurement Supply and Utilisation of Drugs & Consumables and Machinery and Equipments in Himachal Pradesh (2015-2018) - CAG of India (CAG of India)
Assessment of demand for procurement of drugs & consumables and their distribution was neither scientific nor systematic, leading to instances of non-procurement, delay in procurement and non-availability of drugs; and nonissuing, short-issuing, excess issuing of drugs to health institutions. Drugs were purchased irregularly and without requirement resulting in their expiry. Ineffective quality control resulted in distribution of substandard drugs to patients. Procurement of machinery & equipment was not systematic in the absence of any inventory management system leading to cases of non-procurement and procurement without requirement, which resulted in items remaining unutilised/ idle and non-functional. Items were also found to be lying unutilised owing to non-posting of technical staff.
For the Period 2015-2018